Characteristic of professional interests of young workers - Čebelis, J. (Psichologija, 1982)
The article acquaints us with the findings of professional interests of the Vilnius Furniture Centre. All the young workers are divided into four groups and characterized accordingly. The results of the investigation of young workers (up to 25 years of age) have shown that 48.2 percent of them came to the enterprise without any professional interest, 43.6 percent – had the lower (consumer), and 8.2 percent - the higher (worker) level of professional interests. Yet none of them had the highest (specially professional) level of professional interests. It proves the necessity of moulding the professional interests of the young workers.
Keywords: professional interests; workers